Indentation size effect in Knoop and Vickers hardness measurement of dental resin-based composites - Roubickova, A; Tichy, A; Vrbova, R; Bradna, P (Journal of the mechanical behavior of biomedical materials, 2025)
OBJECTIVES: Comparisons of material hardness may be affected by the indentation size effect (ISE), which is characterized by increasing hardness values at decreasing loads. This study aimed to assess the influence of load, dwell time and measurement method on ISE in dental resin-based composites with different filler content. METHODS: Knoop (HK) and Vickers (HV) microindentation hardness of Filtek Ultimate Universal Restorative (FU) and Filtek Supreme Flowable Restorative (FF) was measured under different loads (0.098-2.96 N, i.e. 10-300 gf) and dwell times (5-30 s). Their effects on HK and HV were evaluated using repeated measures ANOVA, which was also used to compare the measurement methods. Coefficients of Meyer's equation, proportional specimen resistance (PSR) model and a modified PSR model were calculated using regression analyses. RESULTS: ISE was more pronounced for the highly-filled FU than for the less-filled FF, and HK was more susceptible to ISE than HV. The effect of dwell time was similar for both materials and measurement methods; hardness values decreased with dwell time, significantly between 5 s and 30 s. SIGNIFICANCE: The possible presence of ISE should be considered when determining measurement conditions for the microindentation hardness of dental resin-based composites. HV was found to be less sensitive to ISE and provided stable hardness values at lower loads than HK. Due to the high variability of composites, any hardness measurement should be preceded by mapping the effect of load to ensure that load-independent hardness is measured. If hardness values continue to decrease in the whole range of increasing loads, load-independent hardness can be calculated using the PSR model.
Keywords: testování materiálů; složené pryskyřice; Materials Testing; testy tvrdosti; Hardness Tests; Composite Resins; Hardness; tvrdost